2017
DOI: 10.1021/acsami.6b13713
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Epsilon-near-Zero Reflectors Enhance the Quantum Efficiency of Thin Solar Cells at Visible and Infrared Wavelengths

Abstract: The engineering of broadband absorbers to harvest white light in thin-film semiconductors is a major challenge in developing renewable materials for energy harvesting. Many solution-processed materials with high manufacturability and low cost, such as semiconductor quantum dots, require the use of film structures with thicknesses on the order of 1 μm to absorb incoming photons completely. The electron transport lengths in these media, however, are 1 order of magnitude smaller than this length, hampering furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Correspondingly, the absorption in the TE case is reduced compared with TM, as can be found in Supplementary Notes 2 the performance. Besides the photothermal experiments demonstrated here, more sophisticated applications related to energy harvesting, such as photovoltaics [33], could be realised based on the artificial leaf. The absolute absorption ability and consequently the photothermal conversion efficiency of the fractal structures may not be as good as some other Au-based absorbers [22,34], especially considering the fabrication complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the absorption in the TE case is reduced compared with TM, as can be found in Supplementary Notes 2 the performance. Besides the photothermal experiments demonstrated here, more sophisticated applications related to energy harvesting, such as photovoltaics [33], could be realised based on the artificial leaf. The absolute absorption ability and consequently the photothermal conversion efficiency of the fractal structures may not be as good as some other Au-based absorbers [22,34], especially considering the fabrication complexity.…”
Section: Discussionmentioning
confidence: 99%
“…We performed fully-dispersive three-dimensional FDTD simulations using our home-made simulator NANOCPP [24][25][26][27][28][29]. In our simulations, the computational domain was organized as follows: the z-aligned nanodisks were placed at the centre of a 2 µm × 2 µm × 1 µm box, with uniaxial perfectly matched layer (UPML) boundary conditions emulating an open system [30].…”
Section: Fdtd Simulationsmentioning
confidence: 99%
“…In particular, it has already been demonstrated that when an antenna is placed on top of an extremely low-permittivity substrate, the air is the "denser" medium with higher relative permittivity and therefore the antenna pattern will be predominantly backscattered into the air [20,21]. Their ability to be good reflectors and, at the same time, provide high electric field values, makes them also good candidates for energy harvesting purposes [22] and photocatalysis [23]. ENZ conditions, which occur when the real part of the dielectric permittivity crosses the zero, may be found in natural (e.g., low loss noble metals, some semiconductors and some polar dielectrics) and artificial materials (metamaterials) alike, where the latter are more flexible both in terms of the zero-crossing wavelength and effective losses [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%